The association between knowledge about HIV and risk factors in young Amazon people - Mariana Souza de Lima; Jaciely Caldas Raniere; Carlos Jaime Oliveira Paes; Lucia Hisako Takase Gonçalves; Carlos Leonardo Figueiredo Cunha; Glenda Roberta Oliveira Naiff Ferreira; Eliã Pinheiro Botelho
ABSTRACT Objectives: analyze the association between the level of HIV knowledge among young people from Amazonas region, their sociodemographic profile and infection risk factors. Methods: cross-sectional analytical study, which used a structured questionnaire containing questions about sociodemographic, behavioral aspects and HIV knowledge. Data were grouped by sex and underwent ordinal and binary logistic regression analysis. Results: the students had an HIV knowledge deficit, associated with a low educational level of their parents and low family income. The most frequent risk factors were lack of knowledge on the part of female students regarding proper male condom use, their infrequent use in sexual relations and failure to do HIV testing. There was an association between level of knowledge and use of dating apps by female students. Conclusions: there was no association between level of knowledge and the preponderant risk factors, but the students' knowledge deficit rendered them more vulnerable to infection.